Adjustment of wheat production to market reform in Egypt - Kherallah, Mylene; Minot, Nicholas; Gruhn, Peter (International Food Policy Research Institute, 1999)
In response to slow growth in the agricultural sector and as part of a general shift towards a more market-oriented economy, the Government of Egypt started liberalizing the agricultural sector in 1987. Controls over wheat production and marketing were eliminated and wheat producer prices were brought closer to international levels. As a result, there has been remarkable increases in wheat crop area and yields, causing wheat production to triple from 1986 to 1998. This study analyzes the results of a survey of 800 Egyptian wheat farmers in order to address three issues that are of interest to agricultural reform policy in Egypt. First, what are the patterns in wheat production and marketing that have emerged following the economic reforms? Second, why is the government unable to purchase more than a small portion of national wheat production? Third, how does wheat supply and input demand respond to wheat and input prices? The survey indicates that Egyptian wheat production is based on small-scale farms, yet these farms are highly commercialized and the use of inputs such as labor, fertilizer and irrigation, is intensive. The government has problems reaching its wheat procurement target because most of the wheat produced is consumed in the rural areas and farmers prefer to sell to traders because of better prices and location. Econometric analysis of the survey data suggests that wheat farmers respond significantly to crop and input prices. The estimated own-price supply elasticity is 0.3, implying that the use of price policy alone to pursue wheat self-sufficiency would be costly and ill-advised.